Tilting of the Australian continent: New evidence from the subsidence and deposition history of the Northern Carnarvon Basin. (March 2022) - Makuluni, Patrick; Hauser, Juerg; Clark, Stuart
Abstract: Studies of global sea-level changes, plate kinematics, marine inundation, and morphology of the continental shelves suggest that the Australian continent has been tilting north eastwards since the Late Cretaceous. Here we investigate the direct impact of this phenomenon and the preceding tectonic events on the evolution of the Northern Carnarvon Basin and discuss their implications for hydrocarbon resources. We use backstripping and decompaction techniques to develop subsidence, sedimentation, and porosity evolution models for the basin, which sits on the axis of the tilt. The goal is to highlight the spatial and temporal variation of subsidence and sedimentation rates and assess their impacts on the porosity of the Early Cretaceous reservoirs within the basin, then give insights into the factors that created accommodation space for sediments. The results reveal a north-eastward shift of subsidence and sedimentation rates within the region. Thus, we observe the highest subsidence rates (∼90 m/Ma) in the southwest (Exmouth and Barrow sub-basins) from Early Jurassic to Early Cretaceous. In the Middle Cretaceous, subsidence and sedimentation moved north-east towards the Dampier (∼40 m/Ma) and some parts of the Barrow sub-basin (∼35 m/Ma). In the Cenozoic era, the highest subsidence rates moved further north-east towards the Beagle sub-basin (∼40 m/Ma) and the North Rankin platform. The results show that the Palaeozoic-Mesozoic rifting events produced higher tectonic subsidence (∼3 km) and higher sediment supply in the southwestern Exmouth and Barrow sub-basins, which reduced towards the north-east in the Dampier and Beagle Sub-basins (∼1.5 km). Subsidence plots along a NE-SW transect and the porosity evolution model results also demonstrate the tilting occurring in these sub-basins. We propose that mantle-driven and subduction-driven tilting of the Australian continent caused the observed local tilting of these sub-basins. Additionally, porosity evolution results provide further information for the definition of periods of hydrocarbon migration in the area. Graphical abstract: Image 1 Highlights: Jurassic syn-rift subsidence propagated north-eastwards from the Exmouth Sub-basin towards the Dampier Sub-basin. The onset of Australian plate tilting (∼75 Ma) coincides with a northeastward change of sedimentation patterns in the NCB. We attribute the Cenozoic subsidence in Dampier and Beagle sub-basins to the mantle-driven northeastward continental tilt. Porosity profiles in the NCB indicate Late Cretaceous regional uplift in the south and subsidence in the northeast.